SEARCH FOR ALTERNATIVE SOURCES OF NATURAL PLANT ANTIOXIDANTS FOR FOOD INDUSTRY - N. V. Kupaeva; E. A. Kotenkova (Пищевые системы)
According to the data of the Food and Agriculture Organization of the United Nations, global food losses are about one third of their total output, mainly due to spoilage. Therefore, a search for safe methods of shelf life extension is an important task, especially for products for specialized nutrition. According to literature data, natural antioxidants can be alternative to existing preservatives due to its ability to inhibit oxidation of the main nutrients. Pulp, seeds and peel of quince, apple «Simirenko», feijoa, persimmon, Jerusalem artichoke, white, red and yellow onion were objects of the study. The total antioxidant capacity was determined by Oxygen Radical Absorbance Capacity (ORAC) and Ferric Reducing Antioxidant Power (FRAP) methods and expressed in µmol equiv. Trolox / g of sample and µmol equiv. Dihydroquercetin / g of sample. It was noticed that peels demonstrated higher antioxidant activity, and red onion husk possessed the highest value, which was 722.8 ± 13.9 µmol equiv. Dihydroquercetin / g of sample and 3357.5 ± 42.2 µmol equiv. Trolox / g of sample. It was shown that the use of fruit and vegetable wastes is promising for production of food-grade antioxidants. In addition, the results of the research could facilitate stimulation of rational and efficient environmental management.